Investıgatıon of Internet Addiction and Anger Expression Styles of Students of the Faculty of Sports Sciences - Yahya Gökhan Yalçin (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: The aim of this study is to examine the Internet Addiction and Anger Expression Styles of students studying at the Faculty of Sport Sciences depending on some variables. Methods: The sample of the study consists of 285 University students, 116 women and 169 men, studying at the Faculty of Sport Sciences at Selçuk University. While the personal information form created by the researcher was used to obtain personal data, the Internet Addiction Scale, developed by Young (1996) and adapted into Turkish by Bayraktar (2001), was used to determine Internet addiction, and The State-Trait Anger Scale (STAS), developed by Spielberger et al. (1983) and whose Turkish validity and reliability was carried out by Özer (1994), was used to determine anger expression styles. Statistical Analysis: Homogeneity and variance of the obtained data were tested, Independent Samples t test was used in pairwise comparisons, One Way Anova test was used in multiple comparisons, and Tukey HSD test was used to determine the source of difference. In this study, Cronbach’s Alpha value was determined as .91 for Internet addiction and .82 for anger expression style. Results: Statistical changes were found in the internet addiction values of the students depending on the factors of gender, daily internet usage time and the field of study (p<0.05). While no statistical change was observed in anger expression styles depending on the field of study factor, statistical changes depending on gender and daily internet usage time factors were found (p<0.05). A positive correlation was determined between internet addiction and anger expression style (p<0.05). Conclusion: As a result, it can be said that men are more internet addicted than women, that daily internet usage time increases anger and internet addiction, and that anger increases as the time allocated to the internet increases